Overcoming China’s animal waste disposal challenge brought by elevated levels of veterinary antimicrobial residues and antimicrobial resistance - Cheng, Grace M.; Cheng, Hefa (Environment international, 2024)
[Display omitted] •Animal manures in China contain high levels of antimicrobials due to overuse in CAFOs.•Manure-based fertilizers are a major source of antimicrobials and AMR in farmlands.•China tried but failed to limit the contents of antimicrobials in organic fertilizers.•Stopping overuse of antimicrobials is the ultimate solution to reduce their residues.•Concerted measures are recommended to reduce antimicrobial use in CAFOs and curb AMR. Direct application of animal waste on farmlands was banned in China recently, rendering organic fertilizer production a sound solution for disposing of animal manures and recycling their materials and nutrients. Due to the overuse of antimicrobials in livestock and poultry farms, manure-based organic fertilizers often contain elevated residues of antimicrobials and abundant antimicrobial resistance genes. Land application of such products has caused significant concerns on the environmental pollution of antimicrobials, and the transmission and development of antimicrobial resistance (AMR), which is a major global health challenge. China’s recent attempt to restrict the contents of antimicrobial residues in organic fertilizers encountered strong resistance from the industry as it would hinder the utilization of animal manures as a raw material. Reducing and even eliminating the use of antimicrobials in animal farms is the ultimate solution to the challenge of manure disposal posed by the elevated levels of antimicrobial residues and AMR. Phasing out the non-therapeutic use of antimicrobials, developing substitutes of antimicrobials, enhancing animal welfare in farms, promoting diversification of animal farms, and developing antimicrobial removal and disinfection technologies for animal waste are recommended to improve the veterinary antimicrobial stewardship and manure management in China’s animal agriculture. These concerted measures would enhance the sustainability of crop and animal farming systems in China and mitigate the impact of antimicrobials and AMR to agro-environmental quality and human health.